INSTRACTIONAL LEADERSHIP AND LEARNING ORGANIZATION AFFECTING SCHOOLS EFFECTIVENESS IN KRABI PROVINCE UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE 13 - เซ่งย่อง, จิราวรรณ; อนันต์นาวี, ภารดี; พฤฑฒิกุล, สถาพร (Academic Journal Phranakhon Rajabhat University, 2018)
The purpose of this research was to study instructional leadership of school administrators and learning organization of school affecting school effectiveness in Krabi province under the secondary educational service area office 13. The research samples were 191 teachers in secondary school, Krabi province under the secondary educational service area office 13. The findings of the research indicate as follows: 1. Schools Effectiveness in Krabi province under the Secondary Educational Service Area Office 13 in overall and each aspecst were a high level. Instructional Leadership of School administrator and learning Organization of school in Krabi province under the Secondary Educational Service Area Office 13 in overall and each aspects were a moderate level. 2. The relationship between Instructional Leadership of School Administrator, Learning Organization of school and Schools Effectiveness in Krabi province under Secondary Educational Service Area Office 13, were related overall and each aspects, rated at high level and found statistically significant at .01 . 3. Instructional Leadership of School Administrator and Learning Organization of school were affecting to schools effectiveness in Krabi province under the Secondary Educational Service Area Office 13 at level of .05. 4. The School Assignment (X11), Academic atmosphere (X13), Team learning (X24), and System Thinking (X25) which can be forecasted schools effectiveness at 54.50 regression equations of the raw score and the regression equations of points in the form of stand score. As follow: Y= .66 + .26X11 + .22X13 + .21 X24 + .15X25 and in the standard equation as X= .28Z11+.23Z13+.23Z24+.14Z25